The growth-employment-poverty nexus in Latin America in the 2000s: Ecuador country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Ecuador experienced moderate economic growth during the 2000s. The economy suffered a mild recession during the international crisis of 2008, but returned to pre-recession GDP per capita level in 2010. Most labour market indicators improved over the period. The only indicator that worsened was the employment structure by occupational position. Most labour market indicators were affected negatively by the international crisis but recovered their pre-crisis levels by 2012. The only exception was labour earnings for some employment categories. With the onset of the crisis of 2008, the poverty rate stopped falling, but it regained its downward trend from 2011 onwards.
Keywords: O15; J01; J30; 330; Ecuador; Latin America; inclusive growth; labour market; poverty